2018
DOI: 10.1186/s12933-018-0683-2
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic variability in continuous glucose monitoring is inversely associated with baroreflex sensitivity in type 2 diabetes: a preliminary report

Abstract: BackgroundIt is presently unclear whether glycemic variability (GV) is associated with baroreflex sensitivity (BRS), which is an early indicator of cardiovascular autonomic neuropathy. The present study is the first to examine the relationships between BRS and GV measured using continuous glucose monitoring (CGM).MethodsThis was a multicenter, prospective, open-label clinical trial. A total of 102 patients with type 2 diabetes were consecutively recruited for this study. GV was assessed by measuring the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 47 publications
5
43
1
Order By: Relevance
“…In fact, we recently reported that in patients with T2DM, there was an association of increased shortterm GV assessed by continuous glucose monitoring with reduced BRS, independently of blood glucose levels. 31) Furthermore, we reported that long-term GV represented by visit-to-visit HbA1c variability over a 2-year period, which is an independent risk factor for CV events, [55][56][57][58] was inversely related to BRS independently of mean HbA1c in patients with T2DM. 59) Details of the mechanism for reduced BRS in patients with T2DM are not yet fully understood.…”
Section: Brs and Variability Of Blood Glucosementioning
confidence: 94%
See 1 more Smart Citation
“…In fact, we recently reported that in patients with T2DM, there was an association of increased shortterm GV assessed by continuous glucose monitoring with reduced BRS, independently of blood glucose levels. 31) Furthermore, we reported that long-term GV represented by visit-to-visit HbA1c variability over a 2-year period, which is an independent risk factor for CV events, [55][56][57][58] was inversely related to BRS independently of mean HbA1c in patients with T2DM. 59) Details of the mechanism for reduced BRS in patients with T2DM are not yet fully understood.…”
Section: Brs and Variability Of Blood Glucosementioning
confidence: 94%
“…[28][29][30] Recently, we reported that the cardio-ankle vascular index, an indicator of arteriosclerosis, was independently associated with BRS. 31) In a carotid bulb containing highly concentrated baroreceptors, increased intima-media thickness was also reportedly associated with reduced BRS. 32) CLINICAL IMPLICATIONS OF BAROREFLEX SENSITIVITY…”
Section: Clinical Features Of Reduced Baroreflex Sensitivitymentioning
confidence: 98%
“…Similarly, in the absence of diabetes, a prediabetic level of fasting blood glucose (Ͼ100 mg/dl) is a better predictor of impaired HR variability and HR turbulence than any other attribute of metabolic syndrome (5). Furthermore, in patients with type 2 diabetes the variability of blood glucose has a highly significant inverse relationship with baroreflex sensitivity (58).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…4,5 In addition, CAN was the strongest predictor for mortality during a 7-year follow-up in people with type 1 diabetes compared with traditional cardiovascular risk factors. 6 Several recent studies indicated that glycaemic variability (GV) is associated with CAN independent of mean glucose in poorly controlled 7,8 and newly diagnosed 9 type 2 diabetes. However, most previous studies on the association between continuous glucose monitoring (CGM)-defined GV and CAN have been conducted in patients with type 2 diabetes, [7][8][9] without dedicated analysis in adults with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%